Congenital hyperinsulinism: clinical cases - I. Yu. Chernyak; E. I. Kleshchenko; E. M. Shadrina; A. S. Alekseenko; I. M. Golovenko (Кубанский научный медицинский вестник, 2022)
Background. Congenital hyperinsulinism (CHI) is a hereditary disorder presenting with the hypersecretion of insulin by pancreatic beta cells and further development of hypoglycaemia. CHI is an orphan disease. According to the European sources, its incidence averages to 1:30,000– 1:50,000 newborns.Clinical Cases Description. This article describes two clinical CHI cases in girls. Case 1: a girl, born on 20.06.2017, was admitted to a paediatric unit of the Children’s Territorial Clinical Hospital for a seizure syndrome. CHI was diagnosed in the age of one month. At 5 months, the girl was confirmed a focal CHI with adenomatous focus localised in pancreatic head; a subtotal head resection has been performed facilitating a compensation. The girl was discharged in a satisfactory condition for a local residence outpatient follow-up. Case 2: the patient was diagnosed with CHI at 1 year 4 months upon admission to an endocrinology unit of the Children’s Territorial Clinical Hospital. The girl was redirected to the National Medical Research Centre for Endocrinology, where CHI was confirmed and indicated for a proglycem treatment. The child was followed-up at the Centre to adjust therapy. In July 2020, a fasting test with background proglycem therapy of 2.9 mg/kg/day (62.5 mg/day) revealed a medicated compensation. The patient was discharged with improvement for a resident endocrinologist follow-up with a recommendation of proglycem at a prescribed dosage upon vital indications.Conclusion. The clinical cases illustrate that, despite rarity and a marked heterogeneity, CHI can be timely diagnosed and properly treated in children. An adequate therapy can facilitate the disease compensation and prevent lifetime neurological complications.